AN ANALYSIS OF SPEAKING ENGLISH AS FOREIGN LANGUAGE ANXIETY OF XI MIPA 4 STUDENTS AT SMAN 3 MANDAU - Winda Vatria Desti; Erni Erni; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This descriptive research aimed to find out the anxiety level of XI MIPA 4 students of SMA N 3 Mandau in speaking english as foreign language. The subjects of this study were XI MIPA 4 students of SMA N 3 Mandau in the academic year 2020/2021. 34 students employed in this study used The Foreign Language Classroom Anxiety Scale questionnaire, developedibyiHorwitzietial.i(1986). Iticonsists of 30 items with 5 points Likert-Scale. The results of the data analysis showed that there were 34 students in class XI MIPA4 of SMAN 3 Mandau whoihadidifferentilevelsiofianxietyiinispeakingiskill. (1) Thereiwere 5istudents (16%) whoiexperience “VeryiAnxious” level, (2) Thereiwere 12 students (29%) who experience “Anxious” level, it means most of XI MIPA 4 students in SMAN 3 Mandau felt Anxious in speaking English, (3) There were 7 students (23%) who experience “Mildly Anxious” level, (4) There were also 7 students (23%) who experience “Relaxed” level, (5) There were 3 students (9%) who experience “Very Relaxed” level in this researchKey Words: Analysis, Anxiety Level, Speaking Ability